Cohort of Phenotype, Genotype, and Outcome of SCN Developmental and Epileptic Encephalopathies from Southern Part of India - Gowda, Vykuntaraju K.; Battina, Manojna; Vegda, Hemadri; Srinivasan, Varunvenkat M.; Chikara, Surendra K.; Mishra, Adrija; Shivappa, Sanjay K.; Benakappa, Naveen (Journal of Pediatric Genetics, 2021)
The SCN encephalopathies are one of the rare early childhood intractable epileptic encephalopathies associated with pleomorphic seizures, cognitive decline, motor, and behavioral abnormalities that begin in early infancy. There is a dearth of data on phenotype and genotype of SCN encephalopathies from the Indian subcontinent, hence we are reporting clinical and molecular profile and outcome of SCN developmental and epileptic encephalopathies. This is a retrospective chart review of SCN developmental and epileptic encephalopathies in a tertiary care center, Bangalore, India between January 2015 and March 2020. All children with clinical features of SCN developmental and epileptic encephalopathies and confirmed with pathogenic variants were included. A total of 50 cases of SCN developmental and epileptic encephalopathies were analyzed, 31 of them were male and the mean age of presentation was 7.8 months. Precipitating factors for the first episode of seizure were fever and vaccination accounting for 33 and 8 children, respectively. Forty (80%) children had prolonged seizures and 15 (30%) had epileptic spasms. All children had a normal birth history and normal development before the onset of seizures, which was followed by developmental delay and regression. Thirty (60%) children had behavioral difficulties, notable hyperactivity, and autistic features. Neuroimaging and the initial electroencephalogram (EEG) were normal in all patients. The mean age of abnormal EEG was 14 months. The various subtypes of SCN variants were SCN1A in 31 children followed by SCN2A and SCN9A in eight children each and SCN1B in three children. Frameshift and nonsense mutations were associated with more severe phenotype and poor outcome compared with missense mutations. Thirty-four patients partially responded to treatment and the rest were refractory. The results of genetic testing were used to guide treatment; sodium channel blocking antiepileptic drugs were discontinued in 15 patients and sodium channel blocking agents were started in 3 patients with partial response. Three out of four children on stiripentol had a partial response. The SCN developmental and epileptic encephalopathies can present with epileptic spasms in addition to other types of seizures. Epileptic spasms are more common in nonsense and frameshift mutations. The outcome is poor in children with epileptic spasms compared with those without epileptic spasms. Genetic testing helps to select antiepileptic drugs that lead to seizure reduction.
Keywords: Dravet syndrome; SCN developmental and epileptic encephalopathies; SCN mutation; epileptic spasms